"Twice the Size of Texas": Assessing the Importance of Regional Popular Music Scenes – A Case Study of Regional Queensland. Issue 5 (20th October 2019) - Bennett, Andy; Cashman, David; Lewandowski, Natalie
ABSTRACT: A healthy popular music scene, it has been suggested, is a key indicator of a healthy society. To date, studies of popular music scenes have largely focused upon urban centers while, in contrast, music scenes in regional and rural contexts have received very little attention. This is in part understandable given the accessible nature of urban scenes to researchers who are often faced with the challenge of working with limited time and resources. Similarly, in smaller countries, for instance, the U.K., or more densely populated ones such as the United States, there is often a less well-developed concept of remoteness. However, in more sparsely populated countries like Australia, the distance between urban centers can be enormous, and even the concept of touring to the next town can be a significant undertaking. This article considers the imperative to study popular music scenes in regional areas. As a case study, it considers Central Queensland, and in particular the areas around the towns of Mackay and Rockhampton. Being Australia's second-largest state, Queensland covers an area of 1.853 million km2 – an area 2.6 times that of Texas.